Onomatope Gijougo dalam Manga I Want to Eat Your Pancreas: Gijougo Onomatopoeia in the I Want To Eat Your Pancreas Manga - Rani Arfianty; Viola Renata Br Togatorop; Amanda Marini Harahap; Jesica Emmenina Octaviani Br Tarigan (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
Onomatopoeia is one of the distinctive features of the Japanese language that functions not only to imitate sounds but also to represent psychological states, emotions, and the inner experiences of characters. In manga, onomatopoeia serves as both a linguistic and a visual element that reinforces the conveyance of meaning. However, previous studies have predominantly focused on giongo (sound-imitating onomatopoeia), while research on gijōgo remains relatively limited. Therefore, this study aims to describe the forms, meanings, and semantic functions of gijōgo found in the manga I Want to Eat Your Pancreas by Yoru Sumino and Izumi Kirihara. This study employs a descriptive qualitative approach using the observation method (simak) and the non-participatory observation technique (Simak Bebas Libat Cakap—SBLC). The data source consists of all dialogues and onomatopoeic expressions found in the two volumes of I Want to Eat Your Pancreas. The data were collected, classified according to the categories of gijōgo, and analysed using a semantic approach while considering the narrative context and the visual elements of the manga. The findings reveal that gijōgo in the manga represents not only positive emotions, such as happiness, warmth, and excitement, through the onomatopoeic expressions ニコッ (niko) and わくわく (wakuwaku), but also negative emotions, including awkwardness, tension, anxiety, surprise, irritation, and hostility, through expressions such as しーん (shiin), ドクン (dokun), ビクッ (biku), イラッ (ira), and ギロッ (giro). The meanings of these onomatopoeic expressions are constructed through the interaction between their linguistic forms, conversational context, characters' facial expressions, and visual illustrations, thereby representing psychological states that are not always explicitly conveyed through dialogue. This study concludes that gijōgo in manga functions not only as a semantic device but also as a narrative device that contributes to characterisation, strengthens the atmosphere, and enables readers to gain a deeper understanding of the characters' emotional development.